2015
DOI: 10.1103/physrevb.92.045101
|View full text |Cite
|
Sign up to set email alerts
|

Twisted gauge theory model of topological phases in three dimensions

Abstract: We propose an exactly solvable lattice Hamiltonian model of topological phases in 3+1 dimensions, based on a generic finite group G and a 4-cocycle ω over G. We show that our model has topologically protected degenerate ground states and obtain the formula of its ground state degeneracy on the 3-torus. In particular, the ground state spectrum implies the existence of purely three-dimensional looplike quasi-excitations specified by two nontrivial flux indices and one charge index. We also construct other nontri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 61 publications
1
101
0
Order By: Relevance
“…G = (G, {1 G }, ∂ : 1 G → 1 G , id). Under this assumption, the model (2.12) reduces to a gauge model, namely the Hamiltonian realization of Dijkgraaf-Witten theory with trivial cohomology class in H 4 (BG, U(1)) [50,51]. The authors showed in [43,45] that in this case the tube algebra for loop-like excitations is isomorphic to the (untwisted) quantum triple algebra, which we reproduce below for convenience:…”
Section: Physical Interpretationmentioning
confidence: 99%
“…G = (G, {1 G }, ∂ : 1 G → 1 G , id). Under this assumption, the model (2.12) reduces to a gauge model, namely the Hamiltonian realization of Dijkgraaf-Witten theory with trivial cohomology class in H 4 (BG, U(1)) [50,51]. The authors showed in [43,45] that in this case the tube algebra for loop-like excitations is isomorphic to the (untwisted) quantum triple algebra, which we reproduce below for convenience:…”
Section: Physical Interpretationmentioning
confidence: 99%
“…In this case, the theory reduces to the Dijkgraaf-Witten (DW) topological gauge theory [51], whose loop braiding statistics has been thoroughly studied [2,3,52].…”
Section: A Twisted Crane-yetter Tqftmentioning
confidence: 99%
“…One is how to develop a similar approach to solve discrete (3+1)-dimensional models [33][34][35] for topological phases. The observable algebra [of local operators that commute with the Hamiltonian, which is the tube algebra in (2+1)-dimensional case] will be expanded due to the extra dimension.…”
Section: Conclusion and Discussionmentioning
confidence: 99%